Specialized journalism and political specialization - Enguix Oliver, Salvador (Mediaciones Sociales, 2015)
This paper reviews the literature on specialized journalism and the traits usually alleged to identify journalistic expertise, normally referred to the content of the texts: thematic specificity, focus in depth, research methodology, use of expert sources, need for additional training for the journalist, segmented hearings, specific textual genres, and linguistic appropriateness. Applying the same factors to political specialization highlights the need to question those traits and consider other criteria in the concept of specialization, referring primarily to professional production routines. It is proposed that in political specialization is the professional practice itself, with its peculiarities and characteristics (relation with sources, knowledge of the system and institutions), which determines the specialization.
Keywords: journalistic sources; specialized journalism; political journalism; professional routines of journalism.